Molecular basis of bilirubin-induced neurotoxicity - Ostrow, JD (2015)
Unconjugated bilirubin (UCB), at slightly elevated unbound concentrations, is toxic to astrocytes and neurons, damaging mitochondria (causing impaired energy metabolism and apoptosis) and plasma membranes (causing oxidative damage and disrupting transport of neurotransmitters). Accumulation of UCB in the CSF and CNS is limited by its active export, probably mediated by MRP1/Mrp1 present in choroid plexus epithelia, capillary endothelia, astrocytes and neurons. Upregulation of MRP1/Mrp1 protein levels by UCB might represent an important adaptive mechanism that protects the CNS from UCB toxicity. These concepts could explain the varied susceptibility of newborns to bilirubin neurotoxicity and the occurrence of neurological damage at plasma UCB concentrations well below therapeutic guidelines, and are relevant to the increasing prevalence of bilirubin encephalopathy in newborns.